Value Engineering Study on Canal Rehabilitation Work Using Cultures in Samarinda Ulu District - Khaldun, Ibnu; Oetomo, Wateno (LPPM of NAROTAMA UNIVERSITY, 2024)
This research was conducted with the aim of analyzing the Engineering Value of Drainage and Culvert Rehabilitation Work in Samarinda Ulu District. The settlement method for this calculation uses Value Engineering Analysis. Value Engineering Analysis is carried out when the Budget Plan (RAB) is still being planned to get maximum results. This research method was carried out in five stages of Value Engineering, namely the information stage, function analysis stage, creative stage, evaluation stage and presentation stage. Weight of each criterion using the Zero-One Method. Zero-One Analysis Matrix Method The zero-one method is used for weighting and assigning scores to criteria. From the results of the analysis it was found that the best alternative that can replace the initial implementation method for selected work items in concrete work is Precast Reinforced Concrete Partially Cast Ready Mix Reinforced Concrete. The cost of concrete work, namely at the beginning or according to plan, is Rp. 623,679,984.00 Costs for concrete work after VE, namely Rp. 271,933,824.09 With costs saved amounting to Rp. 352,393,548.00 or 18.3%. The overall project cost for the initial plan is Rp. 2,099,885,844 while the overall cost of the project after VE is IDR 1,748,139,684. With the cost savings of Rp. Rp. 352,393,548.00 or 16.78% of the total project.